An evaluation of surveillance system for anthrax disease in Gunungkidul District 2020 - Asmi Rizal Abdillah (BKM Public Health and Community Medicine, 2021)
Objective: Recording and reporting fast and precise anthrax cases play an important role in the process of prevention and control of anthrax. Evaluation of the anthrax surveillance system aims to determine the implementation of the anthrax disease surveillance system in the Gunungkidul District. Method: The evaluation design used is a descriptive study. The evaluation subjects are surveillance officers in each community health center and health office was conducted in January - March 2021. We use a checklist and questioner to collect data. The surveillance system attributes were used to assess are simplicity, flexibility, and acceptability. Results: Human resources of community health centers surveillance in Gunungkidul District at the community health centers level are nurses 76.67%, epidemiologists 20%, and midwives 3.33%. The health office level is an epidemiologist. Only 23.33% of surveillance officers have ever attended zoonotic surveillance training. The data collection process conducted by community health centers amounted to 100%. Data processing conduct as much as 87.5% and analysis anthrax case data by 62.5% of the total community health centers. Recording and reporting of anthrax cases from community health centers only 100% of the cases. Dissemination information is not carried out to the maximum on cross-programs. Another identifiable obstacle is that sampling is only done by 18.75% of surveillance officers and is also late. Anthrax management manuals, epidemiological investigation forms, and Standards Operating Procedure (SOP) are also not available in all health centers. Simplicity attributes include ease of facilities (62.5%) and ease of case recapitulation (81.25%). Acceptability attributes: the willingness of people and organizations to participate in reporting anthrax cases (81.25%). Flexible attribute: data/information that can already be used for new needs. Conclusion: The implementation of anthrax surveillance in Gunungkidul District has several disadvantages. It is recommended to periodically monitor and evaluate anthrax surveillance on the implementation of anthrax surveillance.